Comparison of knee joint cartilage thickness in triathletes and physically inactive volunteers based on magnetic resonance imaging and three-dimensional analysis - Muhlbauer, R.; Lukasz, T. S.; Faber, T. S.; Stammberger, T.; Eckstein, F. (The American Journal of Sports Medicine, 2000)
The objective of this study was to employ quantitative magnetic resonance imaging for the analysis of knee joint cartilage thickness in triathletes and physically inactive volunteers. The right knee joints of nine male triathletes (10 hours training per week for at least 3 years) and nine inactive male volunteers (<1 hour of physical activity per week throughout life) were imaged with a previously validated fat-suppressed gradient echo sequence. The cartilage plates were reconstructed three-dimensionally, and the cartilage thickness was computed independently of the original section orientation with a three-dimensional Euclidian distance transformation. There was a high interindividual variability of the mean and the maximal cartilage thickness values in all surfaces, both in the triathletes and in the inactive volunteers. In the patella, the femoral trochlea, and the lateral femoral condyle, the mean and maximal cartilage thickness values were slightly higher in the triathletes, but they were somewhat lower in the medial femoral condyle, and in the medial and lateral tibial plateau. However, the differences did not attain statistical significance. These results are unexpected in view of the functional adaptation observed in other musculoskeletal tissues, such as muscle and bone, in which a more obvious relationship with the magnitude of the applied mechanical stress has been observed.